Environmental & architectural phenomenology. Vol. 2, issue 1 - (:unkn) unknown (Kansas State University. Architecture Department, 1991)
Vol. 2, No. 1, Winter 1991 (includes "citations received,” book review of Sherry Dorward's Design for Mountain Communities, commentary on Gaston Bachelard's Poetics of Space, and essays by David Denton, Louise Million & David Appelbaum).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals